PENERAPAN METODE PENEMUAN TERBIMBING DALAM PEMBELAJARAN MATEMATIKA DI SMA NEGERI 2 PADANG - CHRISTINA KHAIDIR (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Teachers’ domination in teaching Mathematics is one of many factors why students disliked to study it. To solve this problem, a good method has to be promoted in order to improve students’ motivation and their ability in Mathematics. This research was an experimental research through Guide Discovery Method. The subject of the research was the eleventh grade students of Physical Science (IPA) of SMAN 2 Padang who were registered in 2007/2008 academic year. The research result showed that there was different abilities between the students after getting treatment in which the students who were taught through Guide Discovery Method had good abilities rather than the students who were taugh conventionally.Kata kunci: Metode Penemuan Terbimbing, Pembelajaran Matematika